HLA-B and HLA-C loci genetic polymorphism as a marker of severe cutaneous adverse reactions in Thai patients on allopurinol - Sunicha Limkobpaiboon (Chulalongkorn University, 2012)
Thesis (M.Sc. in Pharm.)--Chulalongkorn University, 2009